Interacting evolutionary pressures drive mutation dynamics and health outcomes in aging blood - Kimberly Skead (Nature Portfolio, 2021)
Age-related clonal hematopoiesis is associated with risk for diseases like acute myeloid leukemia (AML), yet it is unclear why some individuals do not progress despite having AML driver mutations. Here, the authors use deep learning and population genetics models to investigate how the interplay of positive and negative selection influences AML progression.